ANALISIS STRATEGI PEMASARAN DIGITAL TERHADAP KEPUTUSAN PEMBELIAN SCARLETT WHITENING BY FELICYA ANGELISTA - Lina Ramadhanti, (2022)
The purpose of this study is to prove the influence of influencer marketing on purchasing decisions and viral marketing on purchasing decisions. This research is a quantitative research with primary data sources. Respondents from this study are consumers who have or are currently using Scarlett Whitening by Felicya Angelista products, with a total of 100 respondents living in the Jabodetabek. This study uses purposive sampling technique as a data collection technique. The data analysis technique in this research is to use descriptive and inferential data analysis. Based on the results of data processing using t-statistics on Smart PLS, there are results from influencer marketing that have a significant effect on purchasing decisions with a path coefficient value of 0.500. And there are also results from viral marketing that have a significant effect on purchasing decisions with a path coefficient value of 0.390.